Comparison of the Effectiveness of the Artpop Project Based Learning Method with the Literacy Room Learning Method - Ilmatus Sa’diyah; Adelia Savitri; Anas Ahmadi; Galuh Fitri Retnosari; Suvriati Vivka Merdana; Nine Alvariqati Varqa A. (Nusantara Science and Technology Proceedings, 2023)
The project-based learning method is a learning method that is considered to provide more learning experiences than other learning methods, such as discussions and lectures in class. In addition, project-based methods can also provide effective learning outcomes. In learning to write articles, both scientific articles and popular articles, a project-based learning method is needed that can improve students' writing skills. For this reason, in writing scientific articles the "literacy space" method is used, while in writing popular articles the artpop method is used. This research was conducted to compare the effectiveness of the two methods. The research methods used are qualitative and quantitative research. Data collection techniques used were documentation, questionnaires, and student scores. Meanwhile, the data were analyzed descriptively qualitatively, and quantitatively. From the comparative studies that have been carried out, the two methods have significant differences and similarities. However, in terms of effectiveness in learning, the Artpop learning method is considered more effective. The difference in the effectiveness of the two is 2.8%. The artpop learning method is more effective because the learning activities carried out are simple. Students only need to change scientific articles that have been published on Google Scholar into popular articles that can be read by the public in simple language. When writing scientific articles, activities are needed that can increase students' understanding in terms of writing titles, introductions, literature reviews, research methods, results and discussions, citations and bibliography. Meanwhile, in writing popular articles, activities are needed to support students' understanding in terms of writing titles, introductions, contents, and closings. The learning methods used appropriately accommodate the needs of these students.